Harmonisasi Hak Kepegawaian dalam Peraturan Perundang-undangan bagi Penyandang Disabilitas Terkait Kuota di Daerah Istimewa Yogyakarta - M. Syafi'ie; Harahap, Nurmalita Ayuningtyas (Jurnal Panorama Hukum, 2020)
AbstractLegal protection related to the rights of persons with disabilities still causes problems due to various regulations concerning persons with disabilities in the Special Region of Yogyakarta (DIY) are still not harmonious. This research tries to xpolre the question, is the regulation regarding employment rights for persons with disabilities relate to fulfilling qootas to become civil servants in DIY harmonious? And what kind of legal remedies should be done as a form of harmonization of laws and regulations regarding the rights of persons with disabilities related to employment rights in DIY? This research is a normative research, that is the research object of study in the form of legal norms. Primary and secondary materials is obtained through literature study, and analysis of the data will be analyzed legally. The result of the study concluded, the regulation of employment rights for person with disabilities relating to minimum amout of recruitment quota in the government agencies in DIY is not harmonius, and legal remedies can be made with legislative review.Key Words: Persons with disabilities, employment rights, harmonization AbstrakPerlindungan hukum terkait dengan hak penyandang disabilitas masih menimbulkan permasalahan, disebabkan oleh berbagai peraturan tentang penyandang disabilitas di Daerah Istimewa Yogyakarta (DIY) masih belum harmonis. Penelitian ini mencoba menggali pertanyaan yaitu, apakah pengaturan mengenai hak kepegawaian bagi penyandang disabilitas terkait pemenuhan kuota untuk menjadi pegawai negeri di DIY sudah harmonis? dan seperti apa upaya hukum yang harus dilakukan sebagai bentuk harmonisasi peraturan perundang-undangan mengenai hak-hak penyandang disabilitas terkait dengan hak kepegawaian di DIY? Penelitian ini merupakan penelitian normatif, yakni penelitian yang obyek kajiannya berupa norma hukum. Bahan primer dan sekunder diperoleh melalui studi kepustakaan. Analisa data akan dianalisis secara yuridis. Hasil penelitian menyimpulkan bahwa, pengaturan hak pekerjaan bagi penyandang disabilitas yang berkenaan dengan besarnya minimal kuota penerimaan pegawai di instansi pemerintahan di DIY belum harmonis dan upaya hukum yang dapat dilakukan dengan legislative review.